2009
DOI: 10.17705/1thci.00007
|View full text |Cite
|
Sign up to set email alerts
|

The Intellectual Advancement of Human-Computer Interaction Research: A Critical Assessment of the MIS Literature (1990-2008)

Abstract: Dennis Galletta was the accepting Senior Editor. This article was submitted on 7/10/2009 and accepted on 8/17/2009. It was with the authors ten days for 2 revisions.Zhang, P, N. Li, M. J. Scialdone, and J. Carey (2009) This paper assesses the intellectual advancement of Human-Computer Interaction (HCI) scholarship as one of the five research streams of the Management Information Systems (MIS) discipline. It particularly demonstrates the vitality and maturity that the HCI stream (or sub-discipline) has achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 13 publications
0
62
0
Order By: Relevance
“…In particular, the review found that fewer than 10% of HCI/MIS studies have focused on social issues and interpersonal relationships. Also, over 80% of the literature has focused on the individual level, and less than 8% has considered cross-level effects (Zhang et al, 2009). Although today it is not uncommon for studies to incorporate some contextual factors in their research models, context -when not entirely ignored -is still either downplayed, focuses on description rather than causal relationships, or is studied in a piecemeal fashion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the review found that fewer than 10% of HCI/MIS studies have focused on social issues and interpersonal relationships. Also, over 80% of the literature has focused on the individual level, and less than 8% has considered cross-level effects (Zhang et al, 2009). Although today it is not uncommon for studies to incorporate some contextual factors in their research models, context -when not entirely ignored -is still either downplayed, focuses on description rather than causal relationships, or is studied in a piecemeal fashion.…”
Section: Discussionmentioning
confidence: 99%
“…As an indication of this trend, 45% of articles published in top-tier IS journals in 2008 focused on HCI issues, and this number increased linearly since 1990 (Zhang et al, 2009). Additionally, HCI research has a place in major IS conference tracks (e.g., ICIS; AMCIS; HICSS), is promoted by special interest groups (e.g., ACM SIGCHI; AIS SIGHCI), appears in special issues of major IS journals (e.g., Journal of MIS: 2005; Journal of the AIS: 2004AIS: , 2006AIS: , and 2007, and has its own dedicated journals (e.g.…”
Section: Is There a Gap In Studying Context In Hci/mis Research?mentioning
confidence: 99%
“…The HCI community in IS has historically focused its efforts on analyzing the impacts of HCI artifacts in business, managerial, organizational, and cultural contexts; less effort has been put into innovative design contributions (Zhang and Li, 2005;Zhang et al, 2009). Recent essays on the future of HCI research by Benbasat (2010) and Lyytinen (2010) particularly call for a greater design focus in research to increase the practical relevance of the HCI contribution.…”
Section: The Importance Of Design Research In Hcimentioning
confidence: 99%
“…Human-Computer Interaction (HCI) Research is concerned with the ways humans interact with information, technologies, and tasks; especially in business, managerial, organizational, and cultural contexts (Zhang et al, 2002). Despite the realization that it is important for HCI research to focus on all issues that occur along the lifecycles of any information and communication technology (ICT) artifacts, IS scholars have traditionally put less effort into the design and development stage and more effort into the use and impact stage (Zhang and Li, 2005;Zhang et al, 2009).We contend that the Design Research stream and the HCI research stream are inherently related and highly overlapping, representing different perspectives and approaches toward similar objects: ICT artifacts that humans interact with for various purposes. It is important to encourage active research efforts to make progress and research contributions at the intersection of these two streams.…”
mentioning
confidence: 99%
See 1 more Smart Citation